Production and marketing of cement in CARICOM (CARICOM Secretariat GeorgetownGY, 1987)
Describes production of cement in Jamaica, Barbados and Trinidad and Tobago noting its steady growth. Examines the CARICOM cement market discussing the pattern of imports, regional consumption and growth in demand. Contains country reports on the cement situation in 11 member states, each discussing inter alia, imports/exports, size and trends in the cement market and construction sector growth rates. Lists major conclusions and recommendations pointing out that regional cement production has grown faster than consumption and demand and that no new capacity should be installed unless reliable export markets are ascertained.
IDS